سیرت نبوی ﷺ کی روشنی میں معاشی استحکام کا تحقیقی مطالعہ: A Research Study of Economic Stability in the light of Prophet’s Biography - Dr. Habib ur Rehman; Dr. Hafiz Abdul Rashid (AL-IDRAK JOURNAL, 2023)
Economy has a lot of importance in human life and no society or ideology can ignore it. Islam has given comprehensive principles to human beings in this chapter. If we study the biography of the Prophet (peace be upon him) from the economic and financial aspect, it is clear that the Prophet (peace be upon him) has given us very comprehensive teachings from both theoretical and practical aspects. From the Prophet's biography, we know that in the case of exclusion from economic and economic activities, not only will it be difficult to fulfil the rights of Allah and the rights of the servants, but also the risk of dispersal of collective life increases. For economic stability, some responsibilities are imposed on the individuals of the society while some responsibilities are imposed on the government of the time. In this regard, it is important for the members of the society to make maximum efforts to keep the wealth safe so that this wealth can be spent as per the need in the future. Moreover, the members of the society should be moderate in spending money on their needs. Apart from this, it is also important to adopt legitimate means to acquire wealth. In order to create economic stability, it is also important that the wages of the labourers are paid immediately after the work is done so that the labourers can easily meet their needs. It is the responsibility of the government of the time not to let any member of the society remain free. It should be mandatory for every individual to learn some skill and work hard to improve their economy. Moreover, hoarding should be strictly prohibited at the time of shortage of anything. In order to meet the needs of the deprived people of society, the government should provide financial support to them from time to time until they are able to earn a living. In this article, all these matters have been explained in the light of seerah (peace be upon him).